rút gọn biểu thức sau đó tính giá trị biểu thức d) x4 – 12x ³ +12x ² -12x +111 tại x=11 giúp mk vs !xin cảm ơn

rút gọn biểu thức sau đó tính giá trị biểu thức
d) x4 – 12x ³ +12x ² -12x +111 tại x=11
giúp mk vs !xin cảm ơn

1 bình luận về “rút gọn biểu thức sau đó tính giá trị biểu thức d) x4 – 12x ³ +12x ² -12x +111 tại x=11 giúp mk vs !xin cảm ơn”

  1. x = 11 -> x + 1 = 12
    -> x^4 – 12x^3 + 12x^2 – 12x + 111
    = x^4 – (x + 1)x^3 + (x + 1)x^2 – (x + 1)x + 111
    = x^4 – x^3 – x^3 + x^3 + x^2 – x^2 – x + 111
    = -x + 111
    = -11 + 111
    = 100
     

    Trả lời

Viết một bình luận

Câu hỏi mới